Gun violence through television and the impact on young adults : an investigation of cultivation theory - Bentz, Nick (University of Wisconsin--Whitewater, 2014)
Over the past thirty years there has been fierce debate over the issue of gun control and gun rights, yet empirical evidence surrounding the issue has been limited. The purpose of the current study was to identify if various television programming cultivates pro-gun and anti-gun culture. Using the lens of cultivation theory, 526 survey responses were analyzed regarding consumption of television in conjunction with pro-gun and anti-gun beliefs. The results of the study found that specific types of television programming are significantly correlated to pro-gun and anti-gun beliefs. However, gender and political affiliation were the most significant indicators of pro-gun and anti-gun support. Lastly, only certain aspects of mean world syndrome were significantly related to television consumption.
This file was last viewed in Microsoft Edge.
Keywords: Gun control--Public opinion; Violence on television; Television programs--Social aspects; Youth--Attitudes